Antimicrobial properties of extracts and compounds isolated from Berberis jaeschkeana - Alamzeb, Muhammad; Khan, Muhammad Rafiullah; Ali, Saqib; Shah, Syed Qaiser; Rashid, Mamoon-Ur- (Bangladesh Journal of Pharmacology, 2013)
The present study was undertaken to evaluate the anti microbial properties of Berberis jaeschkeana Schneid Var. jaeschkeana for the first time. The screening of B. jaeschkeana for its phytochemical constituents showed the presence of alkaloids, glycosides, flavonoids, steroids, saponins reducing sugars and terpenoids. Crude ethanolic extract and different fractions showed good antimicrobial properties. Five compounds isolated for the first time from this plant also showed good antimicrobial properties. Columbamine was found to have excellent antimicrobial properties among all the compounds.